Frozen Baby Octopus (Octopus Membranaceus) Marketing Management - Rahardjo, R. Sugeng; Prayoto, Prayoto; Surahmat, Djoko; Supriyadi, Bambang; Suseno, Dewi Alima Nostalia; Kustiandika, Salsabila (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
This research aims to determine the marketing management of frozen Baby Octopus (Octopus Membranaceus) at PT. BIN Central Java. And to find out the marketing strategy and marketing mix of frozen Baby Octopus (Octopus Membranaceus) at PT. BIN Central Java. This research aims to analyze marketing strategies in marketing management and to determine the marketing mix in marketing management. The research methods used are descriptive methods, SWOT Analysis, and 7Ps with a quantitative approach based on interviews, observation, active participation, and documents. One form of marketing strategy that can support marketing of products to create consumer satisfaction is the use of a (marketing mix).